Globalization and Governance: A Critical Contribution to the Empirics - Simplice Asongu; Uchenna Efobi; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2016)
This study assesses the effect of globalisation on governance in 51 African countries for the period 1996-2011. Ten bundled and unbundled governance indicators and four globalisation variables are used. The empirical evidence is based on Generalised Method of Moments. The following findings are established. First, on political governance, only social globalisation improves political stability while only economic globalisation does not increase voice & accountability and political governance. Second, with regard to economic governance: (i) only economic globalisation significantly promote regulation quality; (ii) social globalisation and general globalisation significantly advance government effectiveness and (iii) economic globalisation and general globalisation significantly promote economic governance. Third, as concerns institutional governance, whereas only social globalisation improves corruption-control, the effects of globalisation dynamics on the rule of law and institutional governance are not significant. Fourth, the impacts of social globalisation and general globalisation are positive on general governance. It follows that: (i) political governance is driven by voice and accountability compared to political stability; (ii) economic governance is promoted by both regulation quality and government effectiveness from specific globalisation angles and (iii) globalisation does not improve institutional governance for the most part. Theoretical contributions and policy implications are discussed.
Keywords: F10; F30; I30; O10; O55; 330; Africa; Governance; Globalization